The blood years - Arnold, Elana K. (Balzer + Bray, an imprint of HarperCollins Publishers, 2023)
From Michael L. Printz honoree & National Book Award finalist Elana K. Arnold comes the harrowing story of a young girl's struggle to survive the Holocaust in Romania. Frederieke Teitler and her older sister, Astra, live in a house, in a city, in a world divided. Their father ran out on them when Rieke was only six, leaving their mother a wreck and their grandfather as their only stable family. He's done his best to provide for them and shield them from antisemitism, but now, seven years later, being a Jew has become increasingly dangerous, even in their beloved home of Czernowitz, long considered a safe haven for Jewish people. And when Astra falls in love and starts pulling away from her, Rieke wonders if there's anything in her life she can count on-and, if so, if she has the power to hold on to it.Then-war breaks out in Europe.First the Russians, then the Germans, invade Czernowitz. Almost overnight, Rieke and Astra's world changes, and every day becomes a struggle: to keep their grandfather's business, to keep their home, to keep their lives. Rieke has long known that she exists in a world defined by those who have power and those who do not, and as those powers close in around her, she must decide whether holding on to her life might mean letting go of everything that has ever mattered to her-and if that's a choice she will even have the chance to make. Based on the true experiences of her grandmother's childhood in Holocaust-era Romania, award-winning author Elana K. Arnold weaves an unforgettable tale of love and loss in the darkest days of the twentieth century-and one young woman's will to survive them.